2019
DOI: 10.1016/j.ica.2018.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of single crystals of a nickel(II) dithiocarbamate complex to nickel sulfide crystals

Abstract: Single crystals of bis(κ 2 S,S′-di(isopropyl)dithiocarbamato) nickel(II) were utilized as a single source precursor for the formation of NiS via thermolysis. The complex decomposed at ~250 °C to form α-NiS exclusively with no β-NiS detected. Analysis of the thermolysis regime using in situ techniques showed that the thermolysis occurs in a single step with the major volatile sideproducts being isopropyl-isothiocyanate and carbon disulfide. The resultant NiS was examined using SEM and TEM to reveal a retention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 70 publications
(82 reference statements)
3
17
0
Order By: Relevance
“…These values match well with the expected 1:1 nickel to sulfur molar ratio. The calculated weight percentages also agree with the reported values determining the formation of αor β-NiS www.nature.com/scientificreports www.nature.com/scientificreports/ phase 52,53 . Elemental mapping of the samples indicate a homogeneous distribution of the two elements in the samples (Figure S7, ESI).…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…These values match well with the expected 1:1 nickel to sulfur molar ratio. The calculated weight percentages also agree with the reported values determining the formation of αor β-NiS www.nature.com/scientificreports www.nature.com/scientificreports/ phase 52,53 . Elemental mapping of the samples indicate a homogeneous distribution of the two elements in the samples (Figure S7, ESI).…”
Section: Resultssupporting
confidence: 87%
“…The reversibility might be influenced by the content of Ni and S present in the system at a specified temperature. It has been reported that, the β-NiS phase is formed when the ratio of Ni:S is in the 64:36-67:33 wt% range, and the α-NiS phase is formed when the ratio of Ni:S is in the 63:37-64:34 wt% range 52,53 . The intricate stoichiometric difference between the two phases makes it very challenging to obtain pure phases in the absence of any surface stabilizing reagents.…”
Section: Resultsmentioning
confidence: 99%
“…Recent insight into this decomposition process comes from in situ X-ray diffraction studies. 177 Single crystals of [Ni(S 2 CN i Pr 2 ) 2 ] decompose in a single step at ca. 250 °C to give α-NiS exclusively, with no β-NiS phase detected.…”
Section: Groupmentioning
confidence: 99%
“…595 Later, the solvothermal decomposition of a related precursor, [Ni(S 2 CNBz 2 ) 3 ][FeCl 4 ], in EN was reported to give iron−nickel sulfide nanoparticles, however, broad PXRD peaks meant their phase could not be determined. 177 Recently, Hogarth and co-workers carried out a detailed study of the solvothermal decomposition of [Fe(S 2 CN i Bu 2 ) 3 ] and [Ni-(S 2 CN i Bu 2 ) 2 ] in OLA, products varying as a function of temperature and SSP concentration. 588 The latter was found to be a key variant.…”
Section: Ternary Metal Sulfidesmentioning
confidence: 99%
See 1 more Smart Citation